Bad behaviour or societal failure? Perceptions of the factors contributing to drivers' engagement in the fatal five driving behaviours. (January 2019) - Salmon, Paul M.; Read, Gemma J.M.; Beanland, Vanessa; Thompson, Jason; Filtness, Ashleigh J.; Hulme, Adam; McClure, Rod; Johnston, Ian
Abstract: The so-called 'fatal five' behaviours (drink and drug driving, distraction and inattention, speeding, fatigue, and failure to wear a seat belt) are known to be the major behavioural contributory factors to road trauma. However, little is known about the factors that lead to drivers engaging in each behaviour. This article presents the findings from a study which collected and analysed data on the factors that lead to drivers engaging in each behaviour. The study involved a survey of drivers' perceptions of the causes of each behaviour and a subject matter expert workshop to gain the views of road safety experts. The results were mapped onto a systems ergonomics model of the road transport system in Queensland, Australia, to show where in the system the factors reside. In addition to well-known factors relating to drivers' knowledge, experience and personality, additional factors at the higher levels of the road transport system related to road safety policy, transport system design, road rules and regulations, and societal issues were identified. It is concluded that the fatal five behaviours have a web of interacting contributory factors underpinning them and are systems problems rather than driver-centric problems. The implications for road safety interventions are discussed. Highlights: The 'fatal five' behaviours are known to be the major behavioural contributory factors to road crashes. A systems ergonomics approach enables identification of the factors influencing engagement in these behaviours. We used a driver survey and road safety expert workshop to identify these influencing factors. The factors identified included issues relating to policy, system design, rules and regulations, and societal issues. The findings show the need to consider wider systemic factors when attempting to prevent road trauma.